ARTHROSCOPIC TREATMENT OF RUPTURES OF THE ROTATOR CUFF - Holibka, Radomir; Kalina, Radim; Pach, Miroslav; Ruzickova, Katherine (Biomedical papers, 2005)
566 patients with shoulder disease were treated at the Clinic of Orthopaedics at the University Hospital Olomouc. Of these, 181 were operated for ruptures of the rotator cuff (RC). They were categorised according to the Gschwend classification, age and gender1. Laterality of the operated limb was also evaluated. Patients with ruptures larger than 4 cm were treated by open operation. 84 shoulders with ruptures classified as Gschwend I, II and IIIa -52 males and 32 females-were treated arthroscopically. The age of the operated patients ranged from 40-60 years. In both genders, the right shoulder was more often affected. Two operating techniques were used: 1) Transosseal refixation of the RC muscle tendons, using RC MITEK anchor implants, 2) ``End to end'' sutures, without implants2-4. Operating time was reduced to 30-40 min. The operating results were evaluated according to the UCLA criteria- University of California Shoulder Rating Score2. 45 patients achieved excellent results (53 %), 35 patients had good results (42 %), and 4 patients (5 %) obtained satisfactory results. None of the patients obtained poor results- a score of less than 20 was poor. Patients felt comfortable following the operation and none had any post-operational complications. The author is convinced, along with others, that arthroscopic suturing of RC ruptures classified I-IIIa allows for rupture treatment that in the past had to be treated by open technique2-5. The deltoid muscle is not affected by arthroscopy. There is normalisation of the patient's movement, pain, force, and rotational stability is comparable to the healthy limb. Treatment time is reduced to a minimum and the patient may soon return to normal daily life.
Keywords: Muscles of the rotator cuff/Rupture etiology/Arthroscopic treatment